Prevalencia de la calcificación del ligamento estilohioideo en radiografías panorámicas de pacientes entre 30 - 70 años atendidos en la facultad de odontología de la Universidad Antonio Nariño -Villavicencio, del 2016 al 2021. (2021)
Introduction. Calcification of the stylohyoid ligament is a rare pathology characterized mainly by an elongation of the styloid process. It affects nearby anatomical structures, causing cervical pain, limitation of movement, among others, and, if left untreated, can be fatal due to compression of the carotid arteries. Objective. T